The Position and Aesthetic Form of Indonesian Detective Fiction after the 1980s within the Landscape of Indonesian Literature - Salam, Aprinus; Zuliana, Rina; Mustofa, Ali (POETIKA, 2025)
After its golden age in the 1980s, Indonesian detective fiction experienced a period of decline during the 1990s. In the following decades, many young writers emerged with their own detective works. However, despite its long history, post-1980 Indonesian detective fiction has continued to receive limited scholarly attention. Its position within academic literary studies remains less prominent compared to other genres that are more frequently discussed in Indonesian literary discourse. This research addresses the problem of how Indonesian detective fiction after the 1980s is positioned within the landscape of Indonesian literature, how the aesthetic forms and ideologies of detective works from each decade are manifested, and how post-1980 Indonesian detective fiction not only transforms in terms of form and position but also becomes a negotiation arena between social, political, and cultural discourses. The study employs a sociological approach to literature, by using Pierre Bourdieu’s theory of the literary field and Terry Eagleton’s aesthetics of ideology, this study offers a novel perspective on how Indonesian detective fiction after the 1980s negotiates market pressures, symbolic capital, and cultural discourse. The findings reveal that, after the 1980s, Indonesian detective fiction shifted from a semi-heteronomous to a semi-autonomous position within the literary field, as seen in the works of S. Mara Gd. (1990), E.S. Ito (2005), and Sabda Armandio (2014). Aesthetically and ideologically, the genre transformed from linear, moralistic narratives to experimental, metafictional, and reflective forms that critique power, history, and social values. Consequently, post-1980s Indonesian detective fiction functions as a negotiation arena where social, political, and cultural elements interact, turning popular entertainment into a medium of social critique.